New vision old challenges : the state of pre-primary education in Bangladesh - Nath, Samir R.; Ahmed, Kazi saleh; Chowdhury, A. M. Raza.; ROY, Goutam; Rahman, M Habibur; Campaign for Popular Education (Organization); European Commission. Delegation to Bangladesh (Dhaka : Campaign for Popular Education, Bangladesh : European Union Delegation to Bangladesh, 2014)
A study report on pre-primary education in Bangladesh.
Includes bibliographical references (pages 123-126) and index.
Keywords: Education, Preschool -- Bangladesh -- Evaluation; Education, Primary -- Bangladesh; Educational surveys -- Bangladesh; Educational tests and measurements -- Bangladesh